pull down to refresh

First thing to notice is that because x never appears continuously in the integral (only in the floor function), the integral itself is equal to the following sum:
\sum_{k=1}^{\infty} \frac{1}{\left\lfloor \sum_{n=1}^{k} \frac{ k(-1)^{t+1}}{n^k} \right\rfloor} 
Second, we can write the interior of the sum as:
(-1)^{k+1} \frac{1}{\left\lfloor k \sum_{n=1}^{k} \frac{1}{n^k} \right\rfloor} 
However, because of the floor function, the denominator is actually just k.
Thus:
\sum_{k=1}^{\infty} \frac{1}{\left\lfloor \sum_{n=1}^{k} \frac{ k(-1)^{t+1}}{n^k} \right\rfloor}  = \sum_{k=1}^{\infty} (-1)^{k+1} \frac{1}{k} = \ln 2